The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.3109/10837459609029891
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Lyophilized Polymer Matrices for Administering Recombinant Human Bone Morphogenetic Protein-2

Abstract: Novel unitary devices, prepared by lyophilization of viscous solutions of sodium carboxymethylcellulose (CMC) and methylcellulose (MC), were evaluated as sustained-release delivery systems for recombinant human bone morphogenetic protein-2 (rhBMP-2). In vitro characterization of the unitary devices, which contained rhBMP-2-loaded poly (d,l lactide-co-glycolide) (PLGA) bioerodible particles (BEPs), was conducted over a 2-month period. Determinations included buffer uptake, mass and molecular weight loss and rhB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Such studies have been elusive partly because of a lack of sterile implantable devices that were capable of controlled release. Lyophilized matrices of MC and CMC, containing PLGA microspheres loaded with rhBMP-2, have been suggested and partially tested as 1 such implant type [16][17][18][19][20][21][22][23][24][25][26]. That work was unable to show statistically significant increases in new bone growth because of the presence of rhBMP-2.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Such studies have been elusive partly because of a lack of sterile implantable devices that were capable of controlled release. Lyophilized matrices of MC and CMC, containing PLGA microspheres loaded with rhBMP-2, have been suggested and partially tested as 1 such implant type [16][17][18][19][20][21][22][23][24][25][26]. That work was unable to show statistically significant increases in new bone growth because of the presence of rhBMP-2.…”
Section: Discussionmentioning
confidence: 68%
“…PLGA microsphere delivery systems for rhBMP-2 have been previously reported [16,[24][25][26]. In a study of various carriers for rhBMP-2 microspheres, Rodgers et al [26] found that methylcellulose elicited more fibrosis than did carboxymethylcellulose (CMC) and that CMC alone (ie, with no added rhBMP-2 microspheres) showed a mild promotion of bone growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, most water –soluble substances are easily released from the carriers 10. Indeed, 40% of BMP in the PLGA particles was released within 3 days after administration 11. Low‐molecular‐weight compounds can overcome these obstacles.…”
Section: Introductionmentioning
confidence: 99%